An evaluation of the effect on depression and anxiety levels of the frequency of providing informing to the relatives of patients treated in intensive care unit - Ünal Kantekin, Çiğdem; Tekeli, Arzu Esen; Kaaraaslan, Özgül; Talih, Gamze; Hacımusalar, Yunus (Journal of Surgery and Medicine, 2019)
Aim: Treatment in the Intensive Care Unit (ICU) is a stressful experience, not only for the patient but also for their family. The aim of the study was to investigate the effects on anxiety and depression levels of the relatives of patients in ICU who were given information once a day or three times a day by the same physician. Methods: In this cross sectional study the relatives of the patients hospitalized in the ICU of two university hospitals were randomly separated into two groups. Group 1 comprised 50 individuals closely related to patients in the ICU and they were given information about the patient once a day. Group 2 comprised 49 individuals closely related to patients in ICU and they were given information 3 times a day at 4-hour intervals. After 7 days, all the participants in Groups 1 and 2 completed the Beck Depression Inventory (BDI) and the Penn State Worry Questionnaire (PSWQ). Results: The BDI points of Group 1 were determined to be statistically significantly higher than those of Group 2 (p<0.01). The PSWQ points of Group 1 were determined to be statistically significantly higher than those of Group 2 (p<0.023). Conclusion: By providing information to the relatives of patients 3 times a day rather than once a day created confidence that the patient was being well cared for, involvement with physician in the decision-making process and the feeling that the physician could be reached, thereby strengthening the physician- family relationship. This leads to lower rates of anxiety and depression.